Analysis of the Israel-Iran Conflict on State Sovereignty and Global Security - Amiruddin Amiruddin; Mochammad Zamroni; Anis Ibrahim; Henny Purwanti; Anton Sujatmiko; Panji Mahardika (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The conflict between Israel and Iran, which peaked in 2025-2026, represents one of the most significant escalations in contemporary geopolitics, affecting the international order. This study aims to analyze the implications of this conflict for the principle of state sovereignty and global security dynamics. Using normative research methods, this study examines international legal regulations, the United Nations Charter, the Geneva Conventions, and the doctrines and opinions of international legal experts to evaluate the legality of Israeli military action against Iranian territory. The analysis focuses on the legal, political, and strategic consequences of significant airstrikes such as Operation Lion's Roar and the attack on the South Pars energy facility. The results show that Israel's unilateral military action has the potential to violate international legal norms, including the principle of the prohibition of the use of force without UN Security Council approval, thus threatening Iran's sovereignty and increasing the risk of a transboundary security crisis. This conflict also destabilizes the global security system by disrupting energy trade routes, such as the Strait of Hormuz, and triggering regional military escalations involving other state actors. This research provides a comprehensive understanding of how bilateral conflicts can have a broad impact on state sovereignty and global security, and emphasizes the need for more effective multilateral legal and diplomatic mechanisms to prevent the escalation of international conflicts.